Pancreatoduodenectomy 1997
DOI: 10.1007/978-4-431-68541-8_49
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoduodenectomy in Seoul National University Hospital

Abstract: This research examines the impact of internationalization on small and medium enterprise (SME) survival, and the direct and moderating effects of technology resources and research and development (R&D) alliances. Our survey examination of 1,612 Korean SMEs reveals that sales internationalization is associated with better survival prospects, suggesting that failure risk does not increase with cross-border sales. In addition, though technology resources provide no direct survival benefits, R&D intensity acts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 107 publications
(115 reference statements)
1
63
1
Order By: Relevance
“…S. coelicolor produces two monofunctional catalases: CatA, an H 2 O 2 -inducible major vegetative catalase, and CatB, a stationary phase-specific catalase inducible by osmotic stress (9,10). In addition, two isoforms of catalaseperoxidase have been detected when cells formed aerial mycelium (26). Transient production of catalase-peroxidase also has been observed in other Streptomyces species.…”
mentioning
confidence: 92%
“…S. coelicolor produces two monofunctional catalases: CatA, an H 2 O 2 -inducible major vegetative catalase, and CatB, a stationary phase-specific catalase inducible by osmotic stress (9,10). In addition, two isoforms of catalaseperoxidase have been detected when cells formed aerial mycelium (26). Transient production of catalase-peroxidase also has been observed in other Streptomyces species.…”
mentioning
confidence: 92%
“…The adenine (A) of VP2 start codon was numbered as 1 and the nucleotide just before the A as -1. RT-PCR and sequencing were performed as described previously [26] except the primer sets for sequencing were as follows: P3, P4, VP2-5 0 , VP2-3 0 , VP2-5UTR-F, VP2-3UTR-R, VP2-389F (289-306: 5 0 -AACTACTGCAGGC-TAGTG-3 0 ), and VP2-932R (932-915: 5 0 -TCCAGTTTGAT GGATGTG-3 0 ).…”
Section: Virus Eggs and Chickensmentioning
confidence: 99%
“…Since then, vvIBDVs have been reported in most countries in the world [1]. In Korea, the first outbreak of IBD was reported in 1980 and a typical vvIBDV was first isolated in 1991 [25,26]. AV strains that showed specific antigenic changes were reported in the United States and some other countries, and it was suggested that classical vaccines do not protect chickens from these variants [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…As an application, we construct an operator to give a negative answer to a problem posed by W. Y. Lee [10].…”
Section: Proofs Of Theorems 25 26mentioning
confidence: 99%